Eine einfache Identität

16/03/2010 - 21:50 von Wolfgang Kirschenhofer | Report spam
Hallo!

Man beweise sum(k=0..floor(n/2)) binom(n,2*k)*(-3)^k = 2^n*cos(n*Pi/3).

Gruß,
Wolfgang Kirschenhofer
 

Lesen sie die antworten

#1 Brian M. Scott
17/03/2010 - 00:00 | Warnen spam
On Tue, 16 Mar 2010 21:50:37 +0100, Wolfgang Kirschenhofer
wrote in
<news: in de.sci.mathematik:

Hallo!

Man beweise sum(k=0..floor(n/2)) binom(n,2*k)*(-3)^k = 2^n*cos(n*Pi/3).



2^n * cos(n * pi/3) Re(2^n exp(n * i * pi/3)) Re((2 exp(i * pi/3))^n) Re((1 + i * sqrt(3))^n) Re(sum_{k=0}^n {C(n, k) * i^k * 3^(k/2)}) sum_{k=0}^floor(n/2) {C(n, 2k) * (-1)^k * 3^k} sum_{k=0}^floor(n/2) {C(n, 2k) * (-3)^k}

Brian

Ähnliche fragen